2021
DOI: 10.1038/s41598-021-94509-6
|View full text |Cite
|
Sign up to set email alerts
|

Low serum magnesium concentration is associated with the presence of viable hepatocellular carcinoma tissue in cirrhotic patients

Abstract: This study aimed to ascertain, for the first time, whether serum magnesium (Mg) concentration is affected by the presence of hepatocellular carcinoma (HCC). We retrospectively enrolled consecutive cirrhotic patients with a diagnosis of HCC (n = 130) or without subsequent evidence of HCC during surveillance (n = 161). Serum levels of Mg were significantly (P < 0.001) lower in patients with HCC than in those without (median [interquartile range]: 1.80 [1.62–1.90] mg/dl vs. 1.90 [1.72–2.08] mg/dl). On multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
(58 reference statements)
1
6
0
Order By: Relevance
“…Moreover, mouse experiments have validated that the growth of primary tumors sequesters Mg from the extracellular environment, leading to hypomagnesemia [60]. Additionally, both our work and other studies have described the higher preference of Mg absorption in tumors than normal tissues, which may raise the possibility of reducing serum Mg levels [60,70]. However, this speculation requires further evidence.…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, mouse experiments have validated that the growth of primary tumors sequesters Mg from the extracellular environment, leading to hypomagnesemia [60]. Additionally, both our work and other studies have described the higher preference of Mg absorption in tumors than normal tissues, which may raise the possibility of reducing serum Mg levels [60,70]. However, this speculation requires further evidence.…”
Section: Discussionsupporting
confidence: 59%
“…Epidemiological studies on the association between serum magnesium and HCC risk are limited. A case‐control study of 130 HCC cases and 161 non‐HCC cases within a cohort of cirrhotic patients because of all causes in Italy reported that cirrhotic patients with HCC had significantly lower levels of serum magnesium than patients with cirrhosis without HCC, suggesting that magnesium might offer certain protection against the development of HCC in patients with cirrhosis 28 . In general, our results derived from a study with prospective design and large sample size were consistent with those in previous studies as described previously.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been no epidemiological studies on serum levels of magnesium, which is more objective and biologically relevant, in relation to HCC risk. Previous reports found that serum magnesium level was lower in patients with cirrhosis and HCC than those without HCC in an Italian population 28 . However, this study was a cross‐sectional study design with a small sample size (total of 291 patients) and diverse underlying risk factors for HCC including HBV, HCV, and alcohol abuse.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Serum Mg c oncentration s often decrease in patients w ith neoplasia regardless of treatments (Sartori et al, 1992). One of the possible reasons for this is that tumors act as Mg traps, thereby disrupting the Mg balance of the body, resulting in a lower serum Mg concentration (Parisse et al, 2021). Low serum Mg status has also been associated with increased inflammation in combination with increased oxidative stress in humans (Nielsen, 2010).…”
Section: The Changes In Serum Trace Element Levels Between the Groupsmentioning
confidence: 99%